2019
DOI: 10.1002/adma.201906027
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Solution‐Processed Organic Photodetector for Near‐Infrared Sensing

Abstract: Sensitive detection of near-infrared (NIR) light enables many important applications in both research and industry. Current organic photodetectors suffer from low NIR sensitivity typically due to early absorption cutoff, low responsivity and/or large dark/noise current under bias. Herein, organic photodetectors based on a novel ultranarrow bandgap non-fullerene acceptor, CO1-4Cl, are presented, showcasing a remarkable responsivity over 0.5 A W-1 in the NIR spectral region (920-960 nm), which is the highest amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
440
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 330 publications
(449 citation statements)
references
References 39 publications
9
440
0
Order By: Relevance
“…OPDs based on CO1-4Cl have been recently used for heartrate monitoring, due to its NIR spectral response of up to 920-960 nm, with a large D* of around 10 12 Jones, at wavelengths of up to 1010 nm (Figure 7a,b). [231] A P3HT:O-IDTBR-based Figure 7. a) Photograph of the heart rate setup using the OPD.…”
Section: The Bulk Heterojunction In Organic Photodetectorsmentioning
confidence: 99%
“…OPDs based on CO1-4Cl have been recently used for heartrate monitoring, due to its NIR spectral response of up to 920-960 nm, with a large D* of around 10 12 Jones, at wavelengths of up to 1010 nm (Figure 7a,b). [231] A P3HT:O-IDTBR-based Figure 7. a) Photograph of the heart rate setup using the OPD.…”
Section: The Bulk Heterojunction In Organic Photodetectorsmentioning
confidence: 99%
“…It is known that the J d of OPDs can be reduced by increasing the thickness of active layer due to the increased R sh , which was verified experimentally by Wu and co-workers. [64] Recently, Huang et al reported PD-OPDs with broadband spectral response of 400 to 1100 nm based on an ultralow-bandgap nonfullerene acceptor CO1-4Cl blended with poly [4,8- [65] The PD-OPDs with a thin active layer (active layer thickness ≈ 87 nm) and a thick active layer (active layer thickness ≈ 300 nm) were fabricated as a comparison to study the J d of PD-OPDs with varied active layer thickness. The J d is efficiently suppressed in the thick PD-OPDs, while the J L is still maintained at reverse bias, as shown in Figure 2d.…”
Section: Thick-film Strategy Based Broadband Pd-opdsmentioning
confidence: 99%
“…In the recent years, new alternatives to classical inorganic semiconductors have garnered a lot of attention. A plethora of applications have been reported based on organic and organicinorganic hybrid semiconductors, among others light emitting diodes, [1,2] field effect transistors, [3][4][5] solar cells, [6,7] energy harvesting devices, [8] photodiodes, [9,10] sensors, and wearable electronics. [11] For the continued improvement of these materials and the devices based on them an important first step is to obtain the density of free charge carriers n, also commonly known as charge carrier density.…”
Section: Introductionmentioning
confidence: 99%